International Conference on Computational Intelligence and Multimedia Applications (ICCIMA 2007) 2007
DOI: 10.1109/iccima.2007.25
|View full text |Cite
|
Sign up to set email alerts
|

Detection of T-Waves in 12-Lead Electrocardiogram

Abstract: A new method for detection of T-waves in 12-lead Electrocardiogram (ECG) using Support Vector Machine (SVM) is presented in this paper. Digital filtering techniques are used to remove power line interference and base line wander present in the ECG signal. SVM is used as a classifier for the detection of T-waves. The performance of the algorithm is evaluated using 50, original simultaneously recorded 12-lead ECG records from the standard CSE ECG database. Significant detection rate of 91% is achieved. The perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…These methods are based on derivative-based algorithms (Holsinger et al 1971), filtering approaches (digital filters (Yu et al 1985), adaptive filters (Soria et al 1998)), mathematical transformations (wavelet (Li C et al 1995, Martinez J P et al 2004, Dumont et al 2010, filter banks (Afonso et al 1999), phasor transform (Martinez A et al 2010)), classification methods (neural network approaches (Hu et al 1993), support vector machine (SVM) (Mehta et al 2008), fuzzy C-means algorithm (Mehta et al 2009)), hidden Markov models (HMM) (Coast et al 1990, Hughes et al 2004a, Hughes et al 2006, Andreao et al 2006a, Andreao et al 2006b, automated method (Christov et al 2007) and mathematical morphology methods (Sun et al 2005). Adaptive filters, wavelet transform, SVM, mathematical morphology methods, HMM and Partially Collapsed Gibbs Sampler (PCGS) (Lin et al 2010, Lin et al 2011a have also been used for P-and T-wave delineation.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are based on derivative-based algorithms (Holsinger et al 1971), filtering approaches (digital filters (Yu et al 1985), adaptive filters (Soria et al 1998)), mathematical transformations (wavelet (Li C et al 1995, Martinez J P et al 2004, Dumont et al 2010, filter banks (Afonso et al 1999), phasor transform (Martinez A et al 2010)), classification methods (neural network approaches (Hu et al 1993), support vector machine (SVM) (Mehta et al 2008), fuzzy C-means algorithm (Mehta et al 2009)), hidden Markov models (HMM) (Coast et al 1990, Hughes et al 2004a, Hughes et al 2006, Andreao et al 2006a, Andreao et al 2006b, automated method (Christov et al 2007) and mathematical morphology methods (Sun et al 2005). Adaptive filters, wavelet transform, SVM, mathematical morphology methods, HMM and Partially Collapsed Gibbs Sampler (PCGS) (Lin et al 2010, Lin et al 2011a have also been used for P-and T-wave delineation.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that sensitivity and specificity values for P and T detection are moderate because it is difficult to detect them as compared to QRS complex features irrespective of the approach or algorithm used. Reliable detection of P and T wave is more difficult than QRS complex detection for several reasons including low amplitudes, low signal-to-noise ratio, amplitude and morphological variability and possible overlapping of the P wave with the QRS complex [6].…”
Section: Resultsmentioning
confidence: 99%
“…The results show that the sensitivity for the peaks of the P, QRS and T waves is higher than 98% and the standard deviation of the mean error for each delineated point is below the tolerances of the Common Standards for Electrocardiography (CSE) committee [35] (s < 2σ CSE , known as "loose criterion"), except for the onset of the P wave, for which this value is 3 ms above. The end of the T wave has the highest mean error but below the tolerance, the proper delineation of this point is a well-known challenge, even for cardiologists and different studies have been developed discussing this issue [36].…”
Section: Journal Of L a T E X Class Files Vol 6 No 1 January 2007mentioning
confidence: 99%